2013
DOI: 10.3748/wjg.v19.i23.3658
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long non-coding RNA expression profiles in gastric cancer

Abstract: AIM:To investigate the expression patterns of long non-coding RNAs (lncRNAs) in gastric cancer. METHODS:Two publicly available human exon arrays for gastric cancer and data for the corresponding normal tissue were downloaded from the Gene Expression Omnibus (GEO). We re-annotated the probes of the human exon arrays and retained the probes uniquely mapping to lncRNAs at the gene level. LncRNA expression profiles were generated by using robust multi-array average method in affymetrix power tools. The normalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 38 publications
8
160
0
2
Order By: Relevance
“…Despite the above findings, our current knowledge about the expression patterns and functional roles of lncRNAs in gastric cancer is still limited. In previous studies, efforts have been made to reannotate the probes of Affymetrix microarrays that match lncRNA sequences in several cancers, including gastric cancer (25). However, this method covers less than 65% of lncRNA genes, and thus should not be considered as unbiased analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above findings, our current knowledge about the expression patterns and functional roles of lncRNAs in gastric cancer is still limited. In previous studies, efforts have been made to reannotate the probes of Affymetrix microarrays that match lncRNA sequences in several cancers, including gastric cancer (25). However, this method covers less than 65% of lncRNA genes, and thus should not be considered as unbiased analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the first time we were able to identify solid tumorassociated lncRNAs not previously implicated in lung cancer as well as uncharacterized lncRNAs altered in lung cancer. For example, linc-UBC1 (LCAL6) was discovered in bladder cancer [32]; UCA1 (LCAL52) in bladder [33], ovarian [46] and breast cancer [47]; LINC00261 (LCAL62) in gastric cancer [31]; ESCCAL-1 (LCAL80) [30] and ENST00000547963 (LCAL84) [34] in esophageal squamous cell carcinoma; CCAT1 (LCAL85) in colon cancer [29]; and PART1 (LCAL92) in prostate cancer [35] and glioblastoma multiforme [48]. Overall, these findings emphasize the importance of unbiased sequencing approaches to better understand the non-coding RNA landscape of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The 111 LCALs include a lncRNA known to play a role in lung cancer (SCAL1 [16]), cancer-associated lncRNAs not previously implicated in lung cancer (CCAT1 [29], ESC-CAL-1 [30], LINC00261 [31], linc-UBC1 [32], UCA1 [33], ENST00000547963 [34], and PART-1 [35]), a lncRNA implicated in a lethal lung developmental disorder (FENDRR [36]), and three previously unannotated lncRNAs. Interestingly, the remaining 99 lncRNAs were previously annotated in normal human tissues but not implicated in human disease.…”
Section: Characterization Of Novel Lncrnasmentioning
confidence: 99%
“…More and more evidence has proved lncRNAs and mRNAs, which may be the most important factors, to result in gastric cancer (10,27,28). Therefore, we evaluated the lncRNAs and mRNAs expression profiles in gastric cancer tissue and corresponding non-tumorous tissues in patients, which was to reveal the potential role of lncRNAs and mRNAs in the pathogenesis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ji-hang Yuan et al (9) observed that the lncRNA-activated by TGF-β (lncRNA-ATB) was up-regulated in hepatocellular carcinoma (HCC) metastases and associated with poor prognosis. Wei-Jun Cao et al (10) identifi ed a set of lncRNAs differentially expressed in gastric cancer by microarray. Qianqian Pang et al (11) showed that the expression level of LINC00152 in gastric carcinoma was signifi cantly increased, compared with matched normal tissue and normal mucosa from healthy controls.…”
Section: Introductionmentioning
confidence: 99%